Repeatability and Heritability of Behavioural Types in a Social Cichlid. (4th May 2011) - Chervet, Noémie; Zöttl, Markus; Schürch, Roger; Taborsky, Michael; Heg, Dik
Abstract : Aim . The quantitative genetics underlying correlated behavioural traits (''animal personality'') have hitherto been studied mainly in domesticated animals. Here we report the repeatability (R ) and heritability (h 2 ) of behavioural types in the highly social cichlid fish Neolamprologus pulcher . Methods . We tested 1779 individuals repeatedly and calculated theh 2 of behavioural types by variance components estimation (GLMM REML), using 1327 offspring from 162 broods from 74 pairs. Results . Repeatability of behavioural types was significant and considerable (0.546), but declined from 0.83 between tests conducted on the same day, to 0.19 on tests conducted up to 1201 days apart. Allh 2 estimates were significant but low (e.g., pair identityh 2 = 0.15 ± 0.03 SE). Additionally, we found significant variation between broods nested within the parent(s), but these were not related to several environmental factors tested. Conclusions . We conclude that despite a considerableR, h 2 in this cichlid species is low, and variability in behavioural type appears to be strongly affected by other (non)genetic effects.